ENaC activation by proteases. (21st March 2022) - Anand, Deepika; Hummler, Edith; Rickman, Olivia J.
Abstract: Proteases are fundamental for a plethora of biological processes, including signalling and tissue remodelling, and dysregulated proteolytic activity can result in pathogenesis. In this review, we focus on a subclass of membrane‐bound and soluble proteases that are defined as channel‐activating proteases (CAPs), since they induce Na + ion transport through an autocrine mechanism when co‐expressed with the highly amiloride‐sensitive epithelial sodium channel (ENaC) in Xenopus oocytes. These experiments first identified CAP1 (channel‐activating protease 1, prostasin) followed by CAP2 (channel‐activating protease 2, TMPRSS4) and CAP3 (channel‐activating protease 3, matriptase) as in vitro mediators of ENaC current. Since then, more serine‐, cysteine‐ and metalloproteases were confirmed as in vitro CAPs that potentially cleave and regulate ENaC, and thus this nomenclature was not further followed, but is accepted as functional term or alias. The precise mechanism of ENaC modulation by proteases has not been fully elucidated. Studies in organ‐specific protease knockout models revealed evidence for their role in increasing ENaC activity, although the proteases responsible for ENaC activation are yet to be identified. We summarize recent findings in animal models of these CAPs with respect to their implication in ENaC activation. We discuss the consequences of dysregulated CAPs underlying epithelial phenotypes in pathophysiological conditions, and the role of selected protease inhibitors. We believe that these proteases may present interesting therapeutic targets for diseases with aberrant sodium homoeostasis.